1999
DOI: 10.1021/es990543c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biodiesel, Biodiesel Blends, and a Synthetic Diesel on Emissions from Light Heavy-Duty Diesel Vehicles

Abstract: Over the past several years, there has been increased interest in reformulated and alternative diesel fuels to control emissions and provide energy independence. In the following study, a California diesel fuel was compared with neat biodiesel, an 80% California diesel/20% biodiesel blend, and a synthetic diesel fuel to examine the effects on emissions. Chassis dynamometer tests were performed on four light heavy-duty diesel trucks using each of the four fuels. The results of this study showed that biodiesel, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
93
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 187 publications
(106 citation statements)
references
References 13 publications
9
93
1
3
Order By: Relevance
“…This is consistent with the results of our previous study on light heavy-duty diesel vehicles that showed a tendency for higher PM emissions with the soy-based biodiesel blends (8).…”
Section: Mass Emission Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the results of our previous study on light heavy-duty diesel vehicles that showed a tendency for higher PM emissions with the soy-based biodiesel blends (8).…”
Section: Mass Emission Resultssupporting
confidence: 93%
“…This work is a follow-up of CE-CERT's previous biodiesel project (8) and also provides ties to CE-CERTs on-going work in testing Hertz equipment rental trucks as part of the ARCO EC-D demonstration program (9).…”
Section: More Recently Arco Has Developed a New Diesel Fuel Called Ementioning
confidence: 99%
See 1 more Smart Citation
“…If errors were identified, they were either corrected or the affected data were not used for data analysis. The procedure includes identifying and correcting problems associated with the ECU data, such as missing or invalid values of manifold absolute pressure (MAP), engine RPM, and intake air temperature (IAT) and associated with the gas analyzers of the PEMS, such as large discrepancies in simultaneous exhaust gas concentration measurements for a given pollutant when comparing the two gas analyzers, "freezing" of the analyzers (failure to update data), occurrence of negative values of emissions that are statistically significantly different from zero, 11 and air leakage into the sampling system based on assessment of the observed air-to-fuel ratio. The latter tends to occur in episodic transient situations when the engine shuts down or turns on during vehicle operation, during which there may be residual infiltrated air in the tailpipe.…”
Section: Data Quality Assurancementioning
confidence: 99%
“…1 The heating value of gasoline is approximately 125,000 BTU/gallon, and its density is 2,790 g/gallon. 11 Thus, each kWh of electricity obtained from the grid corresponds to the potential energy contained in 226 grams of gasoline. On this basis, a gasoline-equivalent fuel economy can be estimated even when the vehicle is operating in part on electricity stored in the plug-in battery from the electrical grid.…”
Section: Data Analysis For Direct and Indirect Energy Usementioning
confidence: 99%